أحوال التشديد في تقدير الغرامة المالية على مخالفي أنظمة ولوائح الدفاع المدني في المملكة العربية السعودية The Conditions of tightening the financial penalty for beaking regulations and rules of the civil defense in Saudi Arabia (in Arabic) - Mazrou, Mohamed; Laeba, Muhammad (Faculity of islamic Scinces, Al -Madinah International University, 2018)
The study aims to clarify the conditions which help Judge or his representative, as a committee member, to consider tightening the financial penalty for breaking regulations and rules of the Civil Defense in Saudi Arabia. The study starts with clarifying the concept of financial penalty, its types and purposes. Then it analyses the conditions mentioned in the article of the Regulations of Civil Defense. The study uses the inductive and analytical approaches. The study concludes that although the conditions are specified in the article of the Regulation, they still need to be reviewed and amended; especially when the committee member faces a situation or an incident with several aspects, such as gravity, repetition and multiplicity. Therefore, the study recommends to update and develop the regulations and rules, especially those relevant to the issue of the articles and paragraphs of Civil Defense.